DAMPAK CLOUD COMPUTING TERHADAP INOVASI BISNIS DIGITAL DI ERA INDUSTRI 4.0 - Prasanti, Devita Aurellia Prasanti; Riono, Sapto Hadi (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
Cloud computing has become a fundamental technology driving digital business innovation in the Industry 4.0 era. This research aims to analyze the impact of cloud computing on digital business innovation in the context of modern industrial transformation through a comprehensive literature study. The method used is a literature study with a descriptive analysis approach to various reference sources relevant to cloud computing, digital transformation, and Industry 4.0 topics. The research results show that cloud computing has achieved an 85% adoption rate among manufacturing companies as one of the top five Industry 4.0 technologies. Cloud computing transforms traditional business paradigms through the transformation from capital expenses to operational expenses models with pay-as-you-go systems, resulting in a 22% improvement in new product time to market and a 21% reduction in lead times. This technology enables democratization of access to advanced infrastructure and facilitates convergence with emerging technologies such as IoT, AI, and machine learning. Nearly 90% of companies now adopt multi-cloud strategies to optimize performance and operational resilience. The conclusion of this research is that cloud computing serves as the main catalyst for digital transformation that enables companies to create connected, agile, and innovative business ecosystems to remain competitive in the Industry 4.0 era.